2020
DOI: 10.1177/1120672120972020
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of corneal shape index in the evaluation of ocular hypertension, primary open-angle glaucoma and exfoliative glaucoma

Abstract: Purpose: The aim of the present study is to calculate Concavity Shape Index (CSI) in patients with POAG and exfoliative glaucoma (XFG) and correlate CSI with the severity of glaucoma, comparing to control and ocular hypertension (OHT) patients. Methods: This was a cross‑sectional study with 146 eyes/146 subjects: 37 healthy eyes, 23 eyes with OHT and 86 glaucoma eyes (70 with POAG, 16 with XFG). The severity of glaucoma was scored with the Glaucoma Staging System 2 (GSS2). Corvis ST® was used to calculate CSI.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
1
1
0
Order By: Relevance
“… 31 , 32 A recent study demonstrated a higher A1DeflL and A2V, and lower A1V compatible with stiffer corneas in OHT eyes, while we found a higher SSI. 33 The differences in corneal biomechanics between OHT eyes and those with glaucoma, either POAG or AG, were evident in the present study. Moreover, OHT eyes usually present a thicker CCT.…”
Section: Discussionsupporting
confidence: 45%
“… 31 , 32 A recent study demonstrated a higher A1DeflL and A2V, and lower A1V compatible with stiffer corneas in OHT eyes, while we found a higher SSI. 33 The differences in corneal biomechanics between OHT eyes and those with glaucoma, either POAG or AG, were evident in the present study. Moreover, OHT eyes usually present a thicker CCT.…”
Section: Discussionsupporting
confidence: 45%
“…On the other hand, factors such as SP-A1, SP-HC, or SSI, which were less affected by IOP, were not included in their analysis [14]. Table 2 summarizes major studies evaluating corneal biomechanics in glaucoma/OHT patients using Corvis ST [33,39,70,[88][89][90][91][92][93][94][95][96][97][98][99][100][101][102][103][104][105][106][107]. Few studies compared the corneal biomechanics of OHT patients versus POAG patients using Corvis ST. Silva and colleagues demonstrated that OHT eyes had less deformable "stiffer" corneas based on significantly higher SP-A1 compared to POAG patients (p = 0.04), although subjects were not stratified into HTG and NTG [103].…”
Section: Clinical Studies Using Corneal Visualization Scheimpflug Tec...mentioning
confidence: 99%